P14.04 Which psychosocial factors are associated with poor sexual health outcomes in women of reproductive age? a systematic review of probability surveys. (13th September 2015) - Edelman, N; de Visser, R; Mercer, C; McCabe, L; Cassell, J
Abstract : Introduction: Interventions such as screening for sexually transmitted infections (STIs) and Contraceptive Advice and Supply (CAS) are increasingly provided in community settings, where populations are heterogeneous in risk. Identification of psychosocial determinants of poor sexual health may inform targeting strategies. We undertook a systematic review to identify psychosocial correlates of STI risk, risky sexual behaviours, unplanned pregnancy and abortion among women in the general population. Methods: We searched 7 databases (PsycInfo, Medline, ASSIA, Cochrane, CINAHL, Web of Science, Embase) to identify probability surveys and baseline longitudinal studies of women aged 16–44 reporting on associations between psychosocial factors and unplanned pregnancy, STI acquisition and sexual risk behaviours. We included studies from the European Union, USA, Canada, Australia, UK or New Zealand between 1/1994–1/2014. Results: Eleven papers were included. Unplanned pregnancy was associated with smoking, depression, relationship status and sexual debut <16 years. Abortion was associated with lack of parental closeness, leaving home at an early age, and abusive experiences. Non-use of contraception was associated with smoking, obesity, relationship status, sedentary lifestyles, and fatalistic attitudes to pregnancy. Condom non-use at first sex was associated with a partner 5+ years older and with less stable partnerships. Multiple partnerships were associated with smoking, drug and alcohol use. STI diagnosis was associated with relationship break-up and young male partners. Conclusion: Relationship status and smoking were the factors most commonly reported to be associated with the adverse sexual health outcomes considered. Psychosocial variables may have utility in identifying women experiencing sexual risk behaviours in community settings, but STIs are too rare in the general population to be identified in this way. We plan to investigate the acceptability of psychosocial questions in targeting, and to explore whether unplanned pregnancy and STI acquisition are associated with different psychosocial factors. Disclosure of interest statement: This work is funded by England's National Institute for Health Research. No pharmaceutical grants or other funds were received in the development of this study.